Housing and integration of internally displaced persons: The case of Ukraine in 2018 - Zavisca, Jane R.; Mitchneck, Beth; Gerber, Theodore P. (Frontiers in Human Dynamics, 2023)
Housing is a widely recognized yet understudied domain of integration of internally displaced persons (IDPs) into their new communities. This article examines the role of housing for integration of Ukrainian IDPs displaced by Russia-fueled political violence in Eastern Ukraine that started in 2014 or by Russia’s annexation of Crimea that year. In Ukraine, housing holds particular significance for integration because homeownership is both widespread and a vital source of people’s sense of wellbeing, security, and normalcy. We find that for IDPs in protracted displacement, deprivation of culturally normative housing conditions, particularly homeownership, impeded both material and experiential housing integration. Our evidence comes from an original 2018 survey of housing experiences of both IDPs and long-term residents in IDPs’ new localities. The survey design enables us to assess housing integration relationally, by comparing gaps in housing status and subjective housing-related wellbeing between IDPs and locals. Disparities in housing status drive differences in subjective experience, ranging from satisfaction with one’s housing to feeling at home in one’s community. These results from our 2018 study may help anticipate challenges of the massive, nationwide displacement crisis precipitated by Russia’s 2022 invasion of Ukraine. Whether Ukrainians resettle in new communities or return to their old ones, divisions between those who have homes to return to and those who do not are likely to be salient. Policies aimed at restoring housing resources, particularly pathways to homeownership, will be essential to rebuilding Ukraine.